Pengaruh Good Corporate Governance (GCG), Corporate Social Responsibility (CSR) dan Ukuran Perusahaan Terhadap Profitabilitas Perusahaan: Studi Kasus pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2021-2023 - Risma Esti Pratiwi; Sri Murwanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to determine and obtain empirical evidence about the influence of Good Corporate Governance, Corporate Social Responsibility, and Company Size on Profitability in Banking Companies listed on the Indonesia Stock Exchange for the period 2021-2023. This study is a quantitative study using secondary data in the form of annual reports of banking companies. The technique used in sampling in this study is purposive sampling. The data analysis techniques used are classical assumption tests and multiple linear regression analysis. The results of this study indicate that good corporate governance has a negative and significant effect on the profitability of banking companies, while corporate social responsibility and company size have a positive and significant effect on profitability. The data analysis used is classical assumption testing and multiple linear regression analysis.The results of this study indicate that good corporate governance has a negative and significant effect on the profitability of banking companies, while corporate social responsibility and company size have a positive and significant effect on the profitability of banking companies.